Praktik Pemberian Salinan Akta Oleh Notaris Yang Minuta Aktanya Belum Ditanda Tangani Secara Lengkap - Alfin Dalfi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2020)
In the routine inspection of the Padang Notary Regional Supervisory Council in 2019, according to his authority in Article 70 letter b UUJN 5 (five) findings of violations were found in the routine inspection of the Notary protocol where there was a violation in the form of incomplete signature of the notary deed. The formulation of this research is why in practice there was a giving of a copy of an act by a notary whose minutes of the deed had not been signed entirely and how the legal consequences of granting a copy of the deed by a notary whose minutes of the act had not been approved in full. This research is analytical descriptive research. Notary Deed has perfect proof of strength in a civil lawsuit, but if it violates specific provisions, the value of the evidence will be degraded to the strength of evidence as a deed under the hand. A notary who is proven to have made a mistake resulting in the act he made only has the power of proof as a deed under the side or even the deed is null and void by law, it will cause harm to the parties.